Knowledge and Practice of Emergency Contraception among Currently-Married Women in Bangladesh: Evidence from a National Cross-Sectional Survey - Alam, Md. Zakiul; Islam, Md. Syful; Sultan, Shafayat (Journal of Population and Social Studies [JPSS], 2020)
More than 30% of the total fertility of 2014 was unwanted in Bangladesh. Emergency contraception (EC) is generally used after sexual intercourse to prevent unintended pregnancy. The objective of this paper is to identify the prevalence, patterns, and determinants of knowledge and practice of EC among currently married reproductive-aged (15-49 year) women in Bangladesh. We employed the data from the nationally representative cross-sectional Bangladesh Demographic and Health Survey 2014. We performed the chi-square test and logistic regression analyses. The knowledge of EC was only 14% among currently married women in 2014. Among the women who know about EC, the prevalence of use was 13.4%, while the incidence was only 6.1%. Age, region, residence, wealth index, media access, and use of modern contraception were the significant determinants of EC. The utilization of EC as a family planning method is crucial in Bangladesh, where the prevalence of unsafe and illegal abortion is present to a great extent. This study has highlighted the necessity of strengthening the structure of family planning service delivery through the exploration of the capacity for increasing knowledge and ensuring utilization of EC in the context of Bangladesh.